Pengembangan Media Pembelajaran Budaya Komering Berbasis Android Menggunakan Kodular SD Negeri Kumpul Rejo - Yanti, Yuli; Devita Sari, Nindy (Universitas Nurul Huda, 2025)
This research discusses the development of an Android-based learning media for Komering culture using the Kodular platform at SDN Kumpul Rejo. The purpose of this study is to develop Android-based learning media for Komering culture using Kodular at SDN Kumpul Rejo. The development of this Android-based learning media for Komering culture is very important to preserve local culture that is starting to be marginalized, to enhance students’ understanding of their own cultural identity through interactive media, and to utilize technology that is already familiar to them. With Kodular, educational media development becomes practical and effective without requiring advanced coding skills, and it also supports the Merdeka Curriculum and the strengthening of the Pancasila Student Profile. This can serve as an example for other regions in promoting cultural identity through education. This research uses the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research instruments used to collect data are unstructured interviews and questionnaires to assess product feasibility. Based on the research results, validation by experts yielded a high usability rating, with an average score of 82.5%, indicating that the developed product is highly feasible to be used as a learning medium.